Costing Study on Incentives Packages for Nepal’s Health Care Professionals - Ministry of Health and Population (Ministry of Health and Population, 2012)
Introduction: The World Health Report from 2000 defines incentives for health workers as "all the rewards and punishments that providers face as a consequence of the organizations in which they work, the institutions under which they operate, and the specific interventions they provide" (WHO, 2000). This study was designed to examine the issue of motivations and incentives from the perspective of an individual or an organizational provider, and focuses on what Adams and Hicks (2000) refer to as external incentives - that is, methods used by health systems to control the activities of health organizations or donors. It is recommended that a mix of incentives be used to attract and retain health care workers to rural areas. Supply side factors (such as well-equipped facilities, and proper sanitation), social and professional factors (opportunities for career development, private practice, educational opportunities for children, good management), and political factors (including political pressure or regional instability) are all likely to affect health worker location preferences (WHO- HPSR, 2008). In addition to these considerations, environmental factors also affect preferences, such as lack of transportation and communication infrastructure, shortage of food grain, and extreme heat or cold. In the changing context of Nepal, the workload of health workers has increased considerably due to the introduction of free care and the growing demand for health care after the popular uprising of 2006. In comparison to the four months prior to free care being implemented, outpatient care utilisation has increased by 70 percent (HMIS) in the four months following implementation.